Electrochemistry of Methylated N‐Confused Free‐Base Tetraarylporphyrins in Nonaqueous Media. Issue 8 (19th April 2017) - Wang, Wenda; Ou, Zhongping; Chen, Minyuan; Zhang, Ying; Fang, Yuanyuan; Kadish, Karl M.
Abstract: Four methylated N‐confused free‐base tetraarylporphyrins, which are represented as N‐CH3 (Ar)4 NcpH2 (Ar =CH3 OPh, CH3 Ph, Ph or ClPh), were synthesized and characterized in terms of their spectral and electrochemical properties in nonaqueous media. The first one‐electron oxidation of each porphyrin is reversible and located at E 1/2 =0.51–0.71 V, whereas the first one‐electron reduction is quasi‐reversible and located between −0.98 and −1.11 V vs. SCE. The electrochemically measured HOMO−LUMO gap ranged from 1.62 to 1.73 V, depending upon the solvent and meso ‐substituents on the macrocycle, and this range of values is similar to the HOMO−LUMO gaps of both the non‐methylated N‐confused porphyrins, (Ar)4 NcpH2 (1.60–1.68 V), and the nitrated N‐confused porphyrins, NO2 (Ar)4 NcpH2 (1.58–1.68 V). The effect of the N‐methyl group on UV/Vis spectra and reduction/oxidation potentials as well as the mechanisms of electron transfer are discussed, and comparisons made with data in the literature for both the non‐methylated N‐confused porphyrins and related N‐confused porphyrins having the same meso ‐substituents and an inner nitro‐substituted carbon atom. Abstract : Understanding the confusion : Four methylated N‐confused free‐base tetraarylporphyrins are synthesized and characterized in terms of their spectral and electrochemical properties in nonaqueous media. The effect of the N‐methyl group on UV/Vis spectra and reduction/oxidation potentials as well as the mechanisms of electron transfer are discussed.